Assessing the phacoemulsification learning curve using duration of each step. Issue 1 (January 2022) - Rali, Aditya; Grosel, Timothy; Fontus, Jerry; Aaron, Maria; Jones, Jeremy; Moore, Elliot; Khalifa, Yousuf M.
Abstract : There is a significant decrease in surgical times for resident cataract cases more than 250 for several steps of cataract surgery, including nuclear disassembly and continuous curvilinear capsulorhexis. Abstract : Purpose: To assess the phacoemulsification learning curve for ophthalmology residents using duration for each step. Setting: Single tertiary, training site hospital. Design: Cross-sectional study. Methods: Emory ophthalmology postgraduate year (PGY) 3 and PGY-4 residents operating at Grady Memorial Hospital between April 2017 and February 2018 were eligible to participate. Duration in seconds for each step of surgery was calculated for incisions, continuous curvilinear capsulorhexis (CCC), hydrodissection, nucleus disassembly, quadrant removal, cortical cleanup, intraocular lens insertion, and closure, and this outcome was analyzed as a function of different experience levels. Results: A total of 528 surgeries were included of 549 total surgeries recorded. 6 categories of experience levels were established as A to F, increasing by increments of 50. There was an overall downward trend across various steps across the 8 case categories, and several adjacent categories demonstrate statistically significant differences. The 3 most time-intensive steps early in training were nucleus disassembly (336.5 ± 16.5 seconds), quadrant removal (275.1 ± 18.0 seconds), and cortical cleanup (244.2 ± 24.6 seconds). There was a sustained drop in mean duration for all steps through at least category D, with most steps showing a drop through category F. Conclusions: There is a benefit to a higher caseload, well above the Accreditation Council for Graduate Medical Education–mandated 86 cases. Improvements in efficiency were observed after 250 cases, with nuclear disassembly and CCC demonstrating a significant decrease in operative time.